12 Rounds in Lo's Gym : Boxing and Manhood in Appalachia - Snyder, Todd, 1981- (Book collections on Project MUSE., 2018)
Questions of class and gender in Appalachia have, in the wake of the 2016 presidential election and the runaway success of Hillbilly Elegy, moved to the forefront of national conversations about politics and culture. From Todd Snyder, a first generation college student turned college professor, comes a passionate commentary on these themes in a family memoir set in West Virginia coal country. 12 Rounds in Lo's Gym is the story of the author's father, Mike "Lo" Snyder, a fifth generation West Virginia coal miner who opened a series of makeshift boxing gyms with the goal of providing local at-risk youth with the opportunities that eluded his adolescence. Taking these hardscrabble stories as his starting point, Snyder interweaves a history of the region, offering a smart analysis of the costs--both financial and cultural--of an economy built around extractive industries. Part love letter to Appalachia, part rigorous social critique, readers may find 12 Rounds in Lo's Gym--and its narrative of individual and community strength in the face of globalism's headwinds--a welcome corrective to popular narratives that blame those in the region for their troubles.